Activation of the aryl hydrocarbon receptor inhibits neuropilin-1 upregulation on IL-2-responding CD4+ T cells - Sandoval, Simone; Malany, Keegan; Thongphanh, Krista; Martinez, Clarisa A.; Goodson, Michael L.; Souza, Felipe Da Costa; Lin, Lo-Wei; Sweeney, Nicolle; Pennington, Jamie; Lein, Pamela J.; Kerkvliet, Nancy I.; Ehrlich, Allison K. (Frontiers in Immunology, 2023)
Neuropilin-1 (Nrp1), a transmembrane protein expressed on CD4+ T cells, is mostly studied in the context of regulatory T cell (Treg) function. More recently, there is increasing evidence that Nrp1 is also highly expressed on activated effector T cells and that increases in these Nrp1-expressing CD4+ T cells correspond with immunopathology across several T cell-dependent disease models. Thus, Nrp1 may be implicated in the identification and function of immunopathologic T cells. Nrp1 downregulation in CD4+ T cells is one of the strongest transcriptional changes in response to immunoregulatory compounds that act though the aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor. To better understand the link between AhR and Nrp1 expression on CD4+ T cells, Nrp1 expression was assessed in vivo and in vitro following AhR ligand treatment. In the current study, we identified that the percentage of Nrp1 expressing CD4+ T cells increases over the course of activation and proliferation in vivo. The actively dividing Nrp1+Foxp3- cells express the classic effector phenotype of CD44hiCD45RBlo, and the increase in Nrp1+Foxp3- cells is prevented by AhR activation. In contrast, Nrp1 expression is not modulated by AhR activation in non-proliferating CD4+ T cells. The downregulation of Nrp1 on CD4+ T cells was recapitulated in vitro in cells isolated from C57BL/6 and NOD (non-obese diabetic) mice. CD4+Foxp3- cells expressing CD25, stimulated with IL-2, or differentiated into Th1 cells, were particularly sensitive to AhR-mediated inhibition of Nrp1 upregulation. IL-2 was necessary for AhR-dependent downregulation of Nrp1 expression both in vitro and in vivo. Collectively, the data demonstrate that Nrp1 is a CD4+ T cell activation marker and that regulation of Nrp1 could be a previously undescribed mechanism by which AhR ligands modulate effector CD4+ T cell responses.